Salmonella Typhimurium derived OMV nanoparticle displaying mixed heterologous O-antigens confers immunogenicity and protection against STEC infections in mice - Xiaoping Bian; Yaolin Chen; Wenjin Zhang; Xinyu Liu; Meihong Lei; Haoxiang Yuan; Mengru Li; Qing Liu; Qingke Kong (Microbial Cell Factories)
Abstract Shiga toxin-producing Escherichia coli (STEC) is one of the major pathogens responsible for severe foodborne infections, and the common serotypes include E. coli O157, O26, O45, O103, O111, O121, and O145. Vaccination has the potential to prevent STEC infections, but no licensed vaccines are available to provide protection against multiple STEC infections. In this study, we constructed an engineered S. Typhimurium to rapidly produce the outer membrane vesicle (OMV) with low endotoxic activity to deliver the O-antigen of E. coli. S. Typhimurium OMV (STmOMV), which displays mixed heterologous O-antigens, was systematically investigated in mice for immunogenicity and the ability to prevent wild-type STEC infection. Animal experiments demonstrated that STmOMV displaying both E. coli O111 and O157 O-antigens by intraperitoneal injection not only induced robust humoral immunity but also provided effective protection against wild-type E. coli O111 and O157 infection in mice, as well as long-lasting immunity. Meanwhile, the O-antigen polysaccharides of E. coli O26 and O45, and O145 and O103 were also mixedly exhibited on STmOMV as O-antigens of the O111 and O157 did. Three mixed STmOMVs were inoculated intraperitoneally to mice, and confer effective protection against six E. coli infections. The STmOMV developed in this study to display mixed heterologous O-antigens provides an innovative and improved strategy for the prevention of multiple STEC infections.